Healing bonds an animal-assisted wellness community for women and children victim-survivors of domestic violence through kinship generative architecture - Morilla, Patricia Ann A.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The legal framework recognized as Republic Act 9262, commonly titled the Anti-Violence Against Women and Their Children Act, was officially instituted on March 8, 2004. It aims to safeguard the rights of women and children within their homes. Despite regulations, service providers' insensitivity and lack of support for women and children survivors result in inadequate facilities that impede their path to recovery. It becomes more difficult for victims to get treatment and start over as a result, leading to psychological and physical health problems such as PTSD, fear, and a lack of trust. According to research, trauma survivors can benefit from animal-assisted therapies. In their path toward healing, this research aims to explore spatial elements that are essential for well-being. The researcher will examine how architectural elements might aid in the healing process for victims and survivors, with a focus on the transformative potential of environments. To address these issues, this study proposes an Animal-Assisted Wellness Community that will show the mutual-beneficial of therapy animals and women and children victims-survivors of domestic violence through architectural interventions. It will also highlight the value of pets in human societies and the physical environments that support their mutual well-being, a review of related literature and precedents, and interviews with professionals were discussed and juxtaposed to identify similarities and differences from previous research and projects. Additional psychosocial therapies that enhance the developmental trajectory of female and juvenile victim-survivors were identified and incorporated into the design.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Include appendices
Keywords: Family violence; Human-animal relationships; Animals -- Therapeutic use